Roland Penrose : the life of a surrealist - King, James, 1942- (Edinburgh University Press, 2016)
The first biography of Roland Penrose, one of the great English-born practitioners of modernism in the twentieth century. 'James King has produced a brilliant analysis of one of the most extraordinary, subtle and complex characters I have ever known. Roland Penrose was ruthless in his pursuit of the best, ruthless with anyone standing in the way of what he wanted to achieve, and yet genuinely tender in his rare ability to explain the art he loved, the art that he wanted you to love. He and his wife, Lee, were my first real tutors in the world of creativity, and I owe them a great and loving debt. This book is not just about a man, it is about an era, a change in our thinking, that in many ways set us free.'-- Julian Fellowes As an artist, an impresario, a biographer and a collector, Roland Penrose (1900-1984) is a key figure in the study of art in England from 1920 to 1984. In the first biography of Penrose, acclaimed biographer James King explores the intricacies of Penrose's life and work tracing the profound effects of his upbringing in a Quaker household on his values, the early influence of Roger Fry, his friendships with Max Ernst, AndrÃ♭ Breton and other surrealists, especially Paul Ã⁹luard, his organization of the landmark International Surrealist Exhibition in the summer of 1936, his conflicted relationship with Pablo Picasso, and his tireless promotion of surrealism as well as the production of his own surrealist art. With a deftness of touch, King traces Penrose's complex professional and personal lives, including his pacifism, his work as a biographer - including his outstanding life of Picasso as well as those of MirÃđ, Man Ray, and TapiÃ·s - and as an art historian, as well as his unconventionality, especially in his two marriages - including that to Lee Miller -and his numerous love affairs. Key Features. The first biography of Roland Penrose and his role in the development of surrealism Evaluates Penrose as an artist in his own right Presents Penrose in the context of a rural modernist environment Points to a deep divide in Penrose between his career as a modernist painter and his work as a promoter of modernism, a chasm central to Penrose's existence